GUARANTEE IN KAFALAH AND RAHN FINANCING AT SHARIA BANK IN INDONESIA - Muhammad Musa; Nia Alfiah; M Mahfuz (Program Studi Perbankan Syari'ah Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2019)
Article 23 paragraph 2 of law number 21 of 2008 concerning Islamic banks expressly states the existence of guarantee and collateral. This is different if you see the provisions of article 8 of law number 10 of 1998 concerning banking, which doesn’t mention the provisions of guarantee and collateral in the article. This implies that there is a meaning as if there was a shift between the two norms. Guarantees and collateral are needed to protect Islamic Banks from risk of non-performing financing and other financial losses that may be caused by fraudulent behavior (moral hazard) from debtors. There must be collateral in the form of tabi’iyah contracts in both the kafalah or the rahn form to secure the fraudulent position of the debtor. Although the use of rahn and kafalah contracts aren’t known in the implementation of musyarakah and mudharabah contracts, but the use of theory of freedom of contract where all parties can still contract in the main dictum because the basic principle of contract is allowed by muamalat fiqh as long as the contract or terms made are not in conflict in sharia. Even Islamic banks have mandate to manage customer funds with the principle of prudence that creditors can generate profits that can be shared with debtors.